TRADISI PACU KUDA DI MINANGKABAU POTRET YANG BERUBAH 1950-1990 (STUDI KASUS PADA MASYARAKAT KABUPATEN TANAH DATAR) - Anwar, Yansen Wapita; Zusmelia, Zusmelia; Nurhuda, Ahmad (Pendidikan Sejarah, 2013)
ABTSRACTTradition Race Horse In Minangkabau Portrait Which Change 1950-1990 Case Study In Sub-Province Tanah Datar. Skripsi Program study Education Of History, STKIP Padang, West Sumatra. 2013.             This Skripsi study about Tradition race horse in Minangkabau generally and Its Tanah Datar of him in the year 1950-1990, besides studying changes race horse also see how its impact from change. Problems of research in formulating as follows: ( 1)what Plain society view to Racing horse ( 2) any kind of change and friction and also its impact in tradition race horse of year 1950-1990 ( 3) How friction of value and meaning race horse to society of Minangkabau specially in Sub-Province Tanah Datar ( 4) Why go down him of animo society to racing downhill horse progressively.             Result of research of that: ( 1) All circle in Tanah Datar almost open on to which are positive because can add economics of society, pride of owner of horse and also also promotion ajang to sub-province executing but to clan of agamais very love the hoisterous of gambling in racing horse. ( 2) Racing horse in Tanah Datar have experiencing of many change and also friction, start from its his arrange management, elite playing it, ( 3) to Plain meaning elite race horse have also changed ahead for the shake of honour now for the shake of money, to public society of Tanah Datar shall no longger lose face otherwise go to look on to race horse ( 4) from internal facet of him race horse shall no longger draw because have happened many change in its execution and shifting it elite playing, less its of horse which follow to race. whereas from external factor of society have thinked is pragmatic, and also have many other entertainment amusement him.